2019
DOI: 10.1136/openhrt-2019-001026
|View full text |Cite
|
Sign up to set email alerts
|

Performing diagnostic radial access coronary angiography on uninterrupted direct oral anticoagulant therapy: a prospective analysis

Abstract: PurposeWe sought to assess the safety of performing diagnostic radial access coronary angiography with uninterrupted anticoagulation on patients receiving direct oral anticoagulant therapy.BackgroundDirect oral anticoagulants have become a popular choice for the prevention of thromboembolism. Risk factors for thromboembolism are common among cardiovascular conditions and indications for direct oral anticoagulant therapy as well as coronary angiography often overlap in patients. It has been hypothesised that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, in a large meta-analysis of patients undergoing cardiovascular endovascular interventions, uninterrupted warfarin was not associated with higher odds of major bleeding compared to interrupted warfarin [18]. Similarly, a prospective analysis involving 49 patients demonstrated that those on uninterrupted direct oral anticoagulants (DOACs) during elective transradial coronary angiography did not have a difference in bleeding (overall 0% major and minor hemorrhage risks in both groups) compared to those not on DOACs [19]. This is worth further clarifying, as almost half of our sample was on a pre-operative anticoagulant/antiplatelet agent, and rates of oral anticoagulant use have been increasing among Medicare beneficiaries [20].…”
Section: Discussionmentioning
confidence: 98%
“…However, in a large meta-analysis of patients undergoing cardiovascular endovascular interventions, uninterrupted warfarin was not associated with higher odds of major bleeding compared to interrupted warfarin [18]. Similarly, a prospective analysis involving 49 patients demonstrated that those on uninterrupted direct oral anticoagulants (DOACs) during elective transradial coronary angiography did not have a difference in bleeding (overall 0% major and minor hemorrhage risks in both groups) compared to those not on DOACs [19]. This is worth further clarifying, as almost half of our sample was on a pre-operative anticoagulant/antiplatelet agent, and rates of oral anticoagulant use have been increasing among Medicare beneficiaries [20].…”
Section: Discussionmentioning
confidence: 98%
“…For NOACs, less data are available. Observational data suggest that both continuation and omittance one day preprocedure may be safe [ 45 , 46 ]. A study comparing patients with AF undergoing primary PCI for STEMI found no difference with regards to in-hospital major bleeding between patients admitted without OAC and those admitted on chronic VKA or NOAC treatment (13.2% vs. 13.0% vs. 11.6%, respectively, p = 0.57) [ 47 ].…”
Section: Peri-procedural Considerations For Pcimentioning
confidence: 99%
“…Chongprasertpon and colleagues also address this pressing topic in their publication 8. This is a prospective study of 49 patients who underwent transradial coronary angiography while on chronic anticoagulant therapy and 49 controls who were not anticoagulated.…”
mentioning
confidence: 99%